(untitled) (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2025)
This research aims to find out the effect of using group discussion on students’ speaking skill at the seventh grade of SMPN 4 Pematangsiantar. This research quantitative with true- experimental method approach. Population of this research was seventh grade with 10 classes which consist of 313 students. And the sample of this research was 64 students in two classes. The technique of collecting data was pre-test and post-test. The technique of analyzing data by using SPSS version 25.0. The result of research was T count (4.553) > T table (1.695) at the significance level α = 0.05 with the degree of freedom (df) = 31. It means that H0 is rejected and H1 is accepted. The post-test score was significantly higher than the pre-test score, indicating that the use of group discussion effectively improves students’ speaking skill. It could be happened that group discussion can be successfully utilized as a learning tool to enhance their confident and teamwork in learning process by giving them stimulation, correcting their pronunciation and also finding the unfamiliar words during teaching. Therefore, group discussion can be considered an effective and enjoyable teaching method for improving speaking skill among junior high school students.